Agronomic traits, ensilability and nutritive value of five pearl millet cultivars grown in a Brazilian semi-arid region. - SANTOS, R. D. dos (2016)
Pearl millet (Pennisetum glaucum(L.) R.) could play an important role as a feed source for ruminants in arid and semi-arid zones of the world owing to its high yield and drought tolerance. The current paper assessed the agronomic characteristics, ensilability, intake and digestibility of five Brazilian pearl millet cultivars (IPA Bulk1BF, BRS 1501, CMS-03, CMS-01 and BN-2) in a typical Brazilian northeastern semi-arid climate. Forage was harvested at the dough stage of grain maturity (growth stage 86 according to the BBCH scale) and ensiled under laboratory and farm conditions. Apparent digestibility of the silages was determined using 25 Santa Inês male lambs. The cultivars CMS-01, CMS-03 and BN-2 out-performed the others in terms of dry matter (DM) and digest- ible DM yield/ha. At DM partitioning among plant tissues, the cultivar IPA Bulk1BF had a greater DM associated with panicles and one of the greatest concentrations of organic matter, lactic acid and in vitro dry matter digestibility among the five cultivars. The cultivar BRS 1501 had greater butyric acid concentration as well as one of the highest pH values. Silage produced from BN-2 not only contained greater acetic acid concentration, but also showed one of the greatest total volatile fatty acid concentrations. There were no differences in feed intake and digestibility of nutrients and fibre fractions across all cultivars. Silage made from BN-2 resulted in greater urinary excretion of nitrogen than those produced from BRS 1501. Under the conditions of the present study, the results obtained for production of DM and digestible dry matter, and the ratio of plant fractions, indicates the possible use of these cultivars for silage production in the Brazilian semi-arid region.